Investigation of the Settlement Of Medical Malpractice Cases in Indonesia Using Criminal Mediation (Comparative Analysis with the United States) - Arsyad, Rahmat Ramadhan (Innovative: Journal Of Social Science Research, 2024)
This essay compares and contrasts the use of prison mediation to resolve medical malpractice claims in the US and Indonesia from a human rights standpoint. This article compares and contrasts the two nations' medical malpractice laws and regulations. Penal mediation is a viable option for swiftly and equitably resolving disputes that take into account the rights guaranteed by human rights. It is critical, however, that victims' rights be not compromised in any way as a result of the mediation agreement. Indonesia might improve the safeguarding of human rights in prison mediation proceedings involving medical misconduct by broadening the mediation's applicability and guaranteeing the participation of reliable and skilled attorneys. The purpose of this research is to compare and contrast the use of criminal mediation to resolve medical malpractice claims in Indonesia and the US from a human rights viewpoint, and to propose reforms to better safeguard human rights throughout this process in Indonesia. Using legal hermeneutics, the study employs a normative juridical comparative approach to inquiry. The study's findings highlight the need of enhancing criminal mediation in Indonesian medical malpractice cases to better address the human rights of all parties involved, particularly in regard to victim identification and equality. For medical malpractice cases to be resolved by criminal mediation, the United States needs clear and comprehensive federal legislation. The resolution of medical malpractice cases in Indonesia via criminal mediation must adhere to the legal idea or principles for preserving human rights. This means that both the victims and the offenders' human rights must be upheld, and the remedies must be fair and compassionate.